CHARACTER EDUCATION MANAGEMENT IN EDUCATIONAL INSTITUTIONS - Zulaikha; Akmaluddin; Siti Mayang Sari; Munawar (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Character education is a system of very important values that must be applied in everyday life, starting from within the family, school, community and country so that they can make a positive contribution to their environment. The era of globalization has had both positive and negative impacts on everyone's lives, including those in the family. In the era of globalization, the family has a big role in shaping the character of children because all the time children have is with the family. Character education is developed through the stages of knowledge (knowing), implementation (acting), and habits (habit). Character education is not limited to knowledge, but reaches into the realm of emotions as well as self-habits.